Characterization and Therapeutic Potential of Bacteriophage-Encoded Polysaccharide Depolymerases with β Galactosidase Activity against Klebsiella pneumoniae K57 Capsular Type - V. Volozhantsev, Nikolay (Antibiotics (Basel), 2020)
Bacteriophages and phage enzymes are considered as possible alternatives to antibiotics in the treatment of infections caused by antibiotic-resistant bacteria. Due to the ability to cleave the capsular polysaccharides (CPS), one of the main virulence factors of Klebsiella pneumoniae, phage depolymerases, has potential in the treatment of K. pneumoniae infections. Here, we characterized in vivo two novel phage-encoded polysaccharide depolymerases as therapeutics against clinical isolates of K. pneumoniae. The depolymerases Dep_kpv79 and Dep_kpv767 encoded by Klebsiella phages KpV79 (Myoviridae; Jedunavirus) and KpV767 (Autographiviridae, Studiervirinae, Przondovirus), respectively, were identified as specific β-galactosidases that cleave the K. pneumoniae K57 type CPS by the hydrolytic mechanism. They were found to be highly effective at combating sepsis and hip infection caused by K. pneumoniae in lethal mouse models. Here, 80–100% of animals were protected against death by a single dose (e.g., 50 μg/mouse) of the enzyme injected 0.5 h after infection by K. pneumoniae strains of the K57 capsular type. The therapeutic effect of the depolymerases is because they strip the capsule and expose the underlying bacterium to the immune attack such as complement-mediated killing. These data provide one more confirmation that phage polysaccharide depolymerases represent a promising tool for antimicrobial therapy.